Preparation method and application of oxygen atom-doped carbon-based iron single-atom catalyst

The preparation of oxygen atom doped carbon-based iron single-atom catalysts through a one-pot method has solved the problem of regulating the doping rate of oxygen atoms in the prior art, and achieved efficient degradation of small molecule pollutants. The catalyst is highly efficient and adjustable. suitable for mass production.

CN117983219BActive Publication Date: 2024-12-20CHINESE RES ACAD OF ENVIRONMENTAL SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202410122897.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-01-29
Publication Date
2024-12-20
Estimated Expiration
2044-01-29

AI Technical Summary

Technical Problem

The prior art is difficult to provide a catalyst synthesis method that can regulate the doping rate of oxygen atoms and thereby improve the efficiency of single-atom catalysts in catalytic persulfate advanced oxidation systems to decompose small molecule pollutants.

Method used

Using a one-pot method, ferrous nitrate nitrate, oxalic acid, melamine and water are mixed and freeze-dried, then calcined under a nitrogen atmosphere, and finally washed with aqueous sulfuric acid solution to prepare an oxygen atom doped carbon-based iron single-atom catalyst (Fe- SAs-ONC catalyst) to regulate the amount of oxygen doping to improve catalytic activity.

Benefits of technology

The oxygen-doped carbon-based iron single-atom catalyst was successfully prepared, which achieved efficient removal of various water pollutants, high catalytic efficiency and strong adjustability, and no organic solvents were used, making it suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117983219B_ABST
    Figure CN117983219B_ABST
Patent Text Reader

Abstract

The present invention provides a preparation method and application of an oxygen atom-doped carbon-based iron single-atom catalyst, belonging to the technical field of single-atom catalysts. The preparation method comprises the following steps: S1, mixing ferric nitrate nonahydrate, oxalic acid, melamine, and water, freeze-drying, and obtaining a precursor; S2, calcining the precursor obtained in step S1 under a nitrogen atmosphere to obtain a catalyst precursor; S3, washing the catalyst precursor obtained in step S2 with an aqueous sulfuric acid solution to obtain an oxygen atom-doped carbon-based iron single-atom catalyst. The preparation method of the present invention is a one-pot method, and no organic solvent is used. The obtained catalyst has a good catalytic oxidation effect of pollutants and has broad application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of single-atom catalysts and relates to a preparation method and application of an oxygen atom-doped carbon-based iron single-atom catalyst. Background Art

[0002] Based on sulfate radicals (·SO 4 2- ) has been widely studied as an effective and environmentally friendly technology for removing refractory pollutants from water. 4 2- It is usually produced by activating persulfate, and has the advantages of long life, wide pH adaptability range, and higher degradation rate of pollutants. Compared with other catalysts, single-atom catalysts have the characteristics of high persulfate activation efficiency, strong stability, and high atomic utilization, and can produce SO 4 2- , hydroxyl radicals, singlet oxygen, high-valent metal species and other active free species to achieve effective degradation and mineralization of pollutants. However, most of the single-atom catalysts prepared so far have symmetrical coordination structures, such as the tetracoordinated MN 4 (M = metal elements such as iron, nickel, cobalt, etc., N = nitrogen) structure, the activation ability of persulfate is limited, further limiting the degradation of pollutants. Studies have reported that breaking the symmetric coordination structure is conducive to regulating the d-band electronic state density of metal elements, and regulating the structure of single-atom catalysts at the atomic level can achieve efficient degradation of pollutants.

[0003] In the article “Study on the activation of persulfate by magnetic nitrogen-doped graphene with multiple active sites” (Chinese Environmental Science, 2021, 41(9): 4127-4134), Yang Liu et al. disclosed a one-pot method for the synthesis of Fe 2 O 3 , Fe 3 N, SA-Fe and N-doped Fe-MNG materials. Among them, Fe-MNG materials have the ability to efficiently adsorb and enrich the model pollutants sulfisoxazole (SIZ), sulfamethoxazole (SMX), meropenem (MEM) and catalyze the decomposition of persulfate to generate sulfate radicals, hydroxyl radicals and singlet oxygen with high oxidation potential, thereby efficiently degrading these organic pollutants. However, the document does not disclose the preparation method of oxygen-doped carbon-based iron single-atom catalysts, nor does it involve the effect of oxygen doping on the degradation of organic pollutants.

[0004] Chinese patent application 202310530294.8 discloses a supported single-atom catalyst, a preparation method and application thereof, and a transition metal single atom supported on the porous carbon through a metal-nitrogen chemical bond; the nitrogen-oxygen doped porous carbon is obtained by calcining a protonate containing nitrogen and oxygen, and the nitrogen content is 9.5-15.7wt%, and the oxygen content is 7.1-8.4wt%. The disclosure uses a protonate containing nitrogen and oxygen, which is lower in cost and easy to obtain, to prepare porous carbon, which reduces the cost, and the transition metal single atom is supported on the porous carbon through a metal-nitrogen chemical bond, which is easy to recover and effectively avoids the large-scale dissolution of metal elements during the catalytic process, so that it has high catalytic activity. The removal rate of the catalyst for bisphenol A, p-nitrophenol, ibuprofen, atrazine, tetracycline hydrochloride and oxytetracycline hydrochloride is greater than 90%. However, the disclosure does not involve a method for effectively regulating the amount of oxygen doping in a single-atom catalytic material, nor does it involve the effect of regulating the amount of oxygen doping on the degradation effect of the catalytic material on organic pollutants.

[0005] Mengxue Yang et al. disclosed a novel method for synthesizing Fe-SAC and Cu-SAC in the article "Versatile pathways for oxidizing organics via peroxymonosulfate activation by different single atom catalysts confining with Fe-N4or Cu-N4 sites" (Chemical Engineering Journal 451(2023)138606). The novel Fe-SAC and Cu-SAC materials were synthesized using lignin extracted from wetland reeds as a carbon source. The synthesized Fe-SAC and Cu-SAC can catalyze persulfate to generate sulfate radicals and hydroxyl radicals, and further catalyze the oxidative degradation of small molecule pollutants such as chloroquine phosphate, ofloxacin, carbamazepine, and sulfamethoxazole. However, the document does not disclose how to effectively regulate the amount of oxygen doping in single-atom catalytic materials, nor does it involve the effect of regulating the amount of oxygen doping on the degradation of organic pollutants by catalytic materials.

[0006] In summary, it is difficult for the existing technology to provide a catalyst synthesis method that can adjust the oxygen atom doping rate and thereby improve the efficiency of single-atom catalysts in catalyzing the decomposition of small molecular pollutants in the persulfate advanced oxidation system. Summary of the invention

[0007] In view of this, the prior art is difficult to provide a catalyst synthesis method that can adjust the oxygen atom doping rate and thereby improve the efficiency of single-atom catalysts in catalyzing the decomposition of small molecule pollutants in persulfate advanced oxidation systems. The present invention aims to provide a preparation method and application of oxygen atom-doped carbon-based iron single-atom catalysts.

[0008] To achieve the above-mentioned object of the invention, on the one hand, the present invention provides a method for preparing an oxygen atom-doped carbon-based iron single-atom catalyst, comprising the following steps:

[0009] S1, mixing ferric nitrate nonahydrate, oxalic acid, melamine and water, and freeze-drying to obtain a precursor;

[0010] S2, calcining the precursor obtained in step S1 under a nitrogen atmosphere to obtain a catalyst precursor;

[0011] S3. Wash the catalyst precursor obtained in step S2 with an aqueous sulfuric acid solution to obtain an oxygen atom-doped carbon-based iron single atom catalyst (Fe-SAs-ONC catalyst).

[0012] Preferably, in step S1, the usage ratio of ferric nitrate nonahydrate, oxalic acid, melamine and water is 1-1.4 g: 1.8-2.2 g: 5 g: 150 mL.

[0013] More preferably, in step S1, the usage ratio of ferric nitrate nonahydrate, oxalic acid, melamine and water is 1.1-1.3 g:1.9-2.1 g:5 g:150 mL.

[0014] More preferably, in step S1, the usage ratio of ferric nitrate nonahydrate, oxalic acid, melamine and water is 1.2 g: 2 g: 5 g: 150 mL.

[0015] Preferably, in step S1, the mixing is specifically stirring and dissolving at 20-50°C.

[0016] More preferably, in step S1, the mixing is specifically stirring and dissolving at 40°C.

[0017] Preferably, in step S1, the freeze-drying temperature is -30°C and the freeze-drying time is 12 hours.

[0018] Preferably, in step S2, the calcination time in the nitrogen atmosphere is 100-500 min.

[0019] More preferably, in step S2, the calcination time in the nitrogen atmosphere is 200-360 min.

[0020] More preferably, in step S2, the calcination time in the nitrogen atmosphere is 360 min.

[0021] Preferably, in step S2, the calcination temperature in the nitrogen atmosphere is 400-800°C.

[0022] More preferably, in step S2, the calcination temperature in the nitrogen atmosphere is 500-700°C.

[0023] More preferably, in step S2, the calcination temperature in the nitrogen atmosphere is 600°C.

[0024] Preferably, in step S3, the concentration of the aqueous sulfuric acid solution is 0.5-2 mol / L.

[0025] More preferably, in step S3, the concentration of the aqueous sulfuric acid solution is 1 mol / L.

[0026] Preferably, in step S3, the washing specifically comprises: mixing the catalyst with an aqueous sulfuric acid solution and stirring.

[0027] More preferably, the stirring is specifically stirring for 24 hours.

[0028] Preferably, after the washing, the mixture is filtered, washed with water until the supernatant is neutral, and the solid is collected and dried.

[0029] More preferably, the collected solids are collected by centrifugation.

[0030] On the other hand, the present invention provides an oxygen atom-doped carbon-based iron single atom catalyst (Fe-SAs-ONC catalyst) prepared by the above preparation method.

[0031] Preferably, the mass percentage of the oxygen atom-doped carbon-based iron single atom catalyst (oxygen element of the Fe-SAs-ONC catalyst) is 7.43%-8.84%.

[0032] On the other hand, the present invention provides the above-mentioned preparation method and application of the above-mentioned oxygen atom-doped carbon-based iron single-atom catalyst in water pollution control.

[0033] Compared with the prior art, the present invention has the following beneficial effects:

[0034] (1) The present invention adopts a one-pot method to successfully prepare an oxygen-doped carbon-based iron single-atom catalyst. The preparation method is simple and the iron atoms are dispersed in single atoms.

[0035] (2) The present invention successfully achieves the regulation of oxygen doping of single-atom catalysts by adding oxalic acid during preparation, and adjusts the d-band electronic state density of metal elements by oxygen doping, thereby achieving an effective improvement in catalyst activity.

[0036] (3) The single-atom catalyst prepared by the present invention can achieve efficient catalytic removal of various types of common water pollutants with high catalytic efficiency and strong adjustability.

[0037] (4) The catalyst preparation method of the present invention does not use organic solvents throughout the process, is easy to scale up for production, and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a transmission electron microscope (TEM) image of the Fe-SAs-ONC catalyst prepared in Example 1.

[0039] Figure 2 This is a high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) image of the Fe-SAs-ONC catalyst prepared in Example 1, in which the position circled by a white circle is single-atom iron.

[0040] Figure 3 This is the EDS-Mapping dark field image of the Fe-SAs-ONC catalyst prepared in Example 1.

[0041] Figure 4 This is the EDS-Mapping element scanning diagram of the Fe-SAs-ONC catalyst prepared in Example 1, wherein the upper left is the scanning diagram of the carbon element (C), the upper right is the scanning diagram of the nitrogen element (N), the lower left is the scanning diagram of the iron element (Fe), and the lower right is the scanning diagram of the oxygen element (O).

[0042] Figure 5 It is the X-ray diffraction pattern of the catalyst prepared by the method in Example 1, Comparative Example 3 and Comparative Example 4. DETAILED DESCRIPTION

[0043] The following non-limiting examples can enable those skilled in the art to more fully understand the present invention, but do not limit the present invention in any way. The following content is only an exemplary description of the scope of the present invention, and those skilled in the art can make various changes and modifications to the invention of the present invention based on the disclosed content, and they should also fall within the scope of the present invention.

[0044] The present invention is further described below by way of specific examples. The various chemical reagents used in the examples of the present invention are obtained through conventional commercial channels unless otherwise specified. Unless otherwise specified, the contents described below are all weight contents. Unless otherwise specified, it is understood that the process is carried out at room temperature.

[0045] In the following examples, the sources of raw materials are shown in Table 1:

[0046] Table 1

[0047]

[0048]

[0049] Example 1

[0050] Synthesis of oxygen-doped single-atom catalysts.

[0051] Add 150mL of water, 1.2g of ferric nitrate nonahydrate, 2g of oxalic acid, and 5g of melamine to a beaker and stir to dissolve at 40°C. Freeze-dry the mixture (-30°C, 12h) to obtain a precursor. Place the precursor in a quartz boat and calcine it at 600°C in a nitrogen atmosphere in a tube furnace for 360min. Naturally cool it to room temperature under nitrogen protection to obtain a catalyst precursor. Mix the catalyst precursor after cooling to room temperature with 50mL of a 1mol / L aqueous sulfuric acid solution and stir for 24h. Filter and centrifuge and wash 3 times with deionized water until the supernatant is neutral. Collect the solid matter and dry it to obtain the Fe-SAs-ONC catalyst.

[0052] The structure of the Fe-SAs-ONC catalyst prepared by the method described in Example 1 is as follows Figure 1-Figure 4 shown. Figure 1 It can be seen that the morphology of the Fe-SAs-ONC catalyst presents a porous structure. Figure 2 It can be seen that the high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) measurement found that the iron element in the Fe-SAs-ONC catalyst exists in the form of atomic metal and there is no obvious aggregation of iron particles, indicating the formation of iron single-atom catalysts. Figure 3 , 4 The EDS-Mapping results show that the iron, carbon, nitrogen and oxygen elements are evenly distributed in the Fe-SAs-ONC catalyst.

[0053] Example 2

[0054] Compared with Example 1, 1.1 g of ferric nitrate nonahydrate and 2.1 g of oxalic acid were used instead, and the rest were the same.

[0055] Example 3

[0056] Compared with Example 1, 1.3 g of ferric nitrate nonahydrate and 1.9 g of oxalic acid were used instead, and the rest were the same.

[0057] Example 4

[0058] Compared with Example 1, 1 g of ferric nitrate nonahydrate and 2.2 g of oxalic acid were used instead, and the rest were the same.

[0059] Example 5

[0060] Compared with Example 1, 1.4 g of ferric nitrate nonahydrate and 1.8 g of oxalic acid were used instead, and the rest were the same.

[0061] Example 6

[0062] Compared with Example 1, an equal volume of 2 mol / L sulfuric acid aqueous solution was used for washing, and the rest was the same.

[0063] Example 7

[0064] Compared with Example 1, an equal volume of 0.5 mol / L sulfuric acid aqueous solution was used for washing, and the rest was the same.

[0065] Example 8

[0066] Compared with Example 1, the calcination temperature was changed to 500° C. for 360 min under nitrogen atmosphere, and the rest were the same.

[0067] Example 9

[0068] Compared with Example 1, the calcination temperature was changed to 700° C. for 360 min under nitrogen atmosphere, and the rest were the same.

[0069] Example 10

[0070] Compared with Example 1, the calcination temperature was changed to 400° C. for 360 min under nitrogen atmosphere, and the rest were the same.

[0071] Embodiment 11

[0072] Compared with Example 1, the calcination temperature was changed to 800° C. for 360 min under nitrogen atmosphere, and the rest were the same.

[0073] Example 12

[0074] Compared with Example 1, the calcination temperature was changed to 600° C. for 200 min in a nitrogen atmosphere, and the rest were the same.

[0075] Embodiment 13

[0076] Compared with Example 1, the calcination temperature was changed to 600° C. for 500 min in a nitrogen atmosphere, and the rest were the same.

[0077] Embodiment 14

[0078] Compared with Example 1, 2.2 g of ferric nitrate nonahydrate and 1 g of oxalic acid were used instead, and the rest were the same.

[0079] Comparative Example 1

[0080] Compared with Example 1, 0.8 g of ferric chloride hexahydrate was used instead of ferric nitrate nonahydrate, and the rest was the same.

[0081] Comparative Example 2

[0082] Compared with Example 1, 2.3 g of malonic acid was used instead of oxalic acid, and the rest was the same.

[0083] Comparative Example 3

[0084] Compared with Example 1, ferric nitrate nonahydrate was not used, and the rest was the same. The obtained catalyst was recorded as ONC catalyst.

[0085] Comparative Example 4

[0086] Compared with Example 1, oxalic acid was not used, and the rest was the same. The obtained catalyst was recorded as Fe-SAs-NC catalyst.

[0087] Comparative Example 5

[0088] Compared with Example 1, the calcination temperature was changed to 300° C. for 360 min under nitrogen atmosphere, and the rest were the same.

[0089] Comparative Example 6

[0090] Compared with Example 1, an equal volume of 0.1 mol / L sulfuric acid aqueous solution was used for washing, and the rest was the same.

[0091] The XRD patterns of the catalysts prepared in Example 1, Comparative Example 3 and Comparative Example 4 are as follows: Figure 5 It can be seen that no obvious metal crystal peak is found in the catalyst, and there is no obvious difference in the XRD pattern from the ONC catalyst not doped with iron (Comparative Example 3), confirming the successful preparation of the single-atom catalyst.

[0092] XPS was used to perform elemental analysis to detect the oxygen element mass content (wt%) in the catalysts prepared in Examples 1-14 and Comparative Examples 1 and 2. The results are shown in Table 2:

[0093] Table 2

[0094] Serial number Oxygen content Serial number Oxygen content Example 1 8.67% Example 8 8.01% Example 2 8.53% Example 9 8.54% Example 3 7.99% Example 10 8.05% Example 4 8.84% Embodiment 11 7.71% Example 5 7.81% Example 12 8.07% Example 6 8.67% Embodiment 13 8.36% Example 7 8.66% Embodiment 14 7.43% Comparative Example 1 7.19% Comparative Example 2 6.88%

[0095] Application Examples

[0096] Using sulfadiazine, mebendazole and indole as model pollutants, the catalytic performance of the catalysts prepared in Examples 1-14 and Comparative Examples 1-6 on the activation of peroxymonosulfate (PMS) was tested.

[0097] The specific experimental methods are as follows:

[0098] Take 5 mg of the catalyst prepared in each example and comparative example, add it to 50 mL of a solution containing 10 mg / L of pollutants and 5 mmol / L of potassium peroxymonosulfonate, and react on a shaker (100 rpm) at room temperature. After 25 minutes, filter using a membrane filter (0.22 μm), take 1 mL of the filtered solution, add 0.5 mL of methanol accurately measured to quench unreacted free radicals, analyze and detect the concentration of the pollutants using liquid chromatography, and calculate the degradation rate of each pollutant within 25 minutes.

[0099] The experimental results are shown in Table 3:

[0100] Table 3

[0101]

[0102]

[0103] Finally, it should be noted that the above content is only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Simple modifications or equivalent substitutions of the technical solution of the present invention by ordinary technicians in this field do not deviate from the essence and scope of the technical solution of the present invention.

Claims

1. A method for preparing an oxygen atom-doped carbon-based iron single-atom catalyst, characterized in that: The following steps are involved: S1, mixing ferric nitrate nonahydrate, oxalic acid, melamine and water, and freeze-drying to obtain a precursor; S2, calcining the precursor obtained in step S1 under a nitrogen atmosphere to obtain a catalyst precursor; S3, washing the catalyst precursor obtained in step S2 with an aqueous sulfuric acid solution to obtain an oxygen atom-doped carbon-based iron single atom catalyst; Wherein, in step S1, the usage ratio of ferric nitrate nonahydrate, oxalic acid, melamine and water is 1-1.4 g: 1.8-2.2 g: 5 g: 150 mL; In step S2, the calcination time in the nitrogen atmosphere is 100-500 min, and the calcination temperature is 400-800° C.; In step S3, the concentration of the aqueous sulfuric acid solution is 0.5-2 mol / L.

2. The preparation method according to claim 1, characterized in that: In step S1, the usage ratio of ferric nitrate nonahydrate, oxalic acid, melamine and water is 1.2 g: 2 g: 5 g: 150 mL.

3. The preparation method according to claim 1, characterized in that: In step S1, the mixing is specifically stirring and dissolving at 20-50°C, the freeze-drying temperature is -30°C, and the freeze-drying time is 12 hours.

4. The preparation method according to claim 1, characterized in that: In step S2, the calcination time in the nitrogen atmosphere is 360 minutes, and the calcination temperature is 600°C.

5. The preparation method according to claim 1, characterized in that: In step S3, the concentration of the aqueous sulfuric acid solution is 1 mol / L.

6. The oxygen atom-doped carbon-based iron single atom catalyst prepared by the preparation method according to any one of claims 1 to 5.

7. Use of the oxygen atom-doped carbon-based iron single-atom catalyst prepared by the preparation method according to any one of claims 1 to 5 or the oxygen atom-doped carbon-based iron single-atom catalyst according to claim 6 in water pollution control.